anonymous
  • anonymous
URGENT! Write an equation in point-slope form for the line through the given point with the given slope. (10,-9); m=-2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
mathstudent55
  • mathstudent55
You need an equation in this form: \(\large y = mx + b\)
anonymous
  • anonymous
okay so do you know y=mx=b
anonymous
  • anonymous
y=mx+b

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

mathstudent55
  • mathstudent55
Let m = the given slope, so m = -2. We now have: \(\large y = -2x + b\)
anonymous
  • anonymous
sorry ;/
Nnesha
  • Nnesha
*point slope* \[\huge\rm y-y_1=m(x-x_1)\]
imqwerty
  • imqwerty
i jst came here to smile :)
mathstudent55
  • mathstudent55
Now put the x and y of your point in the x and y of our equation and solve for b. \(\large y = -2x + b\) \(\large -9 = -2(10) + b\) \(\large -9 = -20 + b\) \(\large 11 = b\) Now that we know b = 11, substitute 11 for b. \(\large y = -2x + b\) \(\large y = -2 x + 11\)
mathstudent55
  • mathstudent55
@Nnesha is correct above. They ask for point-slope, not slope-intercept. \(\large y - y_1 = m(x - x_1) \) \(\large y - (-9) = -2(x - 10)\)

Looking for something else?

Not the answer you are looking for? Search for more explanations.